'Ein sonderbar' Ding': Music, the Historical and the Problem of Temporal Representation in Der Rosenkavalier. (July 2020) - Taylor, Benedict
Abstract: Der Rosenkavalier is an opera that foregrounds time: the problem of time, as transience, passing and ultimately death for the aging Marschallin, and a potentially more redemptive quality, the category of the Augenblick associated with the young lovers Octavian and Sophie, in which the temporal intersects with the eternal. It is also a work that has traditionally marked the turning point in Strauss's relation to historical time and the idea of musical progress, as the composer supposedly retreated from the modernity of Salome and Elektra to a more conservative idiom. The temporal qualities manifested in Der Rosenkavalier invite comparison with another work from this period that similarly foregrounds the concept of time, Thomas Mann's Der Zauberberg . In this self-styled 'novel of time', Mann raises a number of problems concerning the human limitations on perceiving time and its artistic representation, especially with regard to music. Disputing the contention of the narrator of Mann's novel that music cannot 'narrate time', I show that Strauss's music in fact exemplifies music's capacity to express 'the historical in time', using Der Rosenkavalier as a case study for addressing the philosophical problem of temporal representation in art. I argue that Der Rosenkavalier – both Hofmannsthal's text and Strauss's music – is in several significant ways 'an opera about time' – the temporal and the eternal, the historical and what I call the 'metahistorical'.